2022
DOI: 10.1080/10872981.2022.2149252
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mentoring relationships in undergraduate longitudinal general practice tracks – a qualitative study on the perspective of students and general practitioners

Abstract: Background Longitudinal general practice tracks have been established in medical faculties in Europe and worldwide to attract more graduates to general practice careers. In many programs, long-term mentoring relationships play an important role in providing students with positive role models, regular practical experiences, and acquisition of clinical skills in a community context. However, little is known about students’ and general practitioner mentors’ expectations, experiences, challenges, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Similarly, others have also shown that mentees value mentors' support to their work-life balance which came through in this evaluation [39]. Furthermore, much of the literature focuses on the importance of having a caring and supportive relationship where guidance and communication are key, similarly to what we found in this evaluation [39,45]. However, the HRP Alliance mentorship programme had a very specific aim of providing support and skills development as part of researchers' professional development, but which did not include a specific output or development of research skills.…”
Section: Plos Onesupporting
confidence: 72%
“…Similarly, others have also shown that mentees value mentors' support to their work-life balance which came through in this evaluation [39]. Furthermore, much of the literature focuses on the importance of having a caring and supportive relationship where guidance and communication are key, similarly to what we found in this evaluation [39,45]. However, the HRP Alliance mentorship programme had a very specific aim of providing support and skills development as part of researchers' professional development, but which did not include a specific output or development of research skills.…”
Section: Plos Onesupporting
confidence: 72%
“…Building efficient information systems for accessing psychotherapeutic medicines timely, collaborating with psychologists and psychiatrists, and sharing the experience on screening, diagnosis, and treatment of common mental disorders were effective [ 22 , 26 ]. In medical education, long-term mentoring was widely applied and showed a good effect on independent medical tasks, and enabled mentors to provide guidance, resources, encouragement, constructive criticism, and support to their mentees [ 36 ]. A whole-course mentoring system, in which mentors summarize and solve the main problems during the standardized training, could improve self-efficacy and job satisfaction for graduated nurses [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar to the suggestion in literature (6), it was emphasized that the implementation of role models and personal insights help increase attractivity of general practice to students. Other recommendations -like the importance of a long-term one-to-one mentoring program (19) or the integration of a teaching app (10) -were not mentioned in our interviews. A new insight is the demand for new teaching methods such as symptom-based learning, lessons with simulated patients and the integration of case reports.…”
Section: Comparison With Literaturementioning
confidence: 99%